The Recurrence Algorithm for GDOP and Positioning Solution in GPS - Chang Qing Liu Zhongkan Zhang QiShan (Tongxin xuebao)
This paper proves theoretically that GDOP decreases as the number of satellite increases and proposes two recurrence algorithms for calculating the GDOP and positioning solution.These algorithms not only can recursively calculate the GDOP and positioning solution at the same time,but also is very flexible in obtaining the best four satellite positioning solution,the best five satellite positioning solution and the all visible satellite positioning solution according to given requirements.Since the algorithms does not involve the multiplication and inverse of matrix,a fewer calculations are needed.